THE ELECTRIC ENERGY IN FIGHT WITH WEEDS - Toporkov, V.; Korolev, V. (Energy and Automation, 2016)
The analysis of the last studies in the field of use the electric energy for deleting weed and development unit on this base is organized. ecological clean technology and technological scheme of the fight with rubbish vegetation with use electric pulse high power is offered. Results of the studies on influence high-tension кистевых category in ground on provocation of the germination семян weed residing in arable layer are brought. Optimum electric parameters and state of working installation for электроимпульсного of the destruction to rubbish vegetation are motivated.